2020
DOI: 10.1111/eip.13090
|View full text |Cite
|
Sign up to set email alerts
|

Health literacy of people living with mental illness or substance use disorders: A systematic review

Abstract: Aim Health literacy is one's ability to use cognitive and social skills to access, understand and appraise health information. Despite poor health outcomes of people living with mental illness there is limited research assessing their health literacy. This systematic review aims to synthesise research on health literacy rates, conceptualizations, and outcomes of people living with mental illness, including substance use disorders. This will provide insights into how health literacy might be targeted to reduce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 33 publications
0
26
0
Order By: Relevance
“…This could be of benefit to investigate the effects of psychosis on education attainment, general literacy, alongside the consequences of transgenerational trauma, underemployment and social disadvantage to inform development of targeted psychiatric and social interventions in this group [ 57 ]. Finally, another area for focus given the current paucity of literature, as highlighted by the recent systematic review, is the impact of low HL in those living with SMI on health care utilisation and civic engagement [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be of benefit to investigate the effects of psychosis on education attainment, general literacy, alongside the consequences of transgenerational trauma, underemployment and social disadvantage to inform development of targeted psychiatric and social interventions in this group [ 57 ]. Finally, another area for focus given the current paucity of literature, as highlighted by the recent systematic review, is the impact of low HL in those living with SMI on health care utilisation and civic engagement [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review of health literacy in people living with mental illness, identified a paucity of studies. This is complicated in interpretation by small studies and further limited by the use of a broad variety of measures which cannot be compared, ranging from functional HL assessments, such as the S-TOFHLA and The Rapid Estimate of Adult Literacy in Medicine (REALM), to multidimensional surveys [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Community-based studies from LMICs have revealed the relationship between low socioeconomic status (SES) and common mental disorders [20][21][22][23]. Recent literature revealed that low socioeconomic status was linked to lower health literacy with higher stigma [24,25] and lack of mental health help-seeking [26]. Additionally, low-income individuals' perceptions of the structural issues attributed to inefficient government or discrimination may subsequently influence their decision-making and mental health [27].…”
Section: Introductionmentioning
confidence: 99%
“…Recent literature revealed that low socioeconomic status was linked to lower health literacy with higher stigma (24,25) and lack of mental health help-seeking (26). Additionally, low-income individuals' perceptions of the structural issues they encountered may subsequently influence their decision-making, thus influencing mental health (27).…”
Section: Introductionmentioning
confidence: 99%